Comparative Analysis of Modern Mobile Applications for Accounting and Control of Medicines in Everyday Life - Datsok, Y.; Yakovleva, O. (Національний технічний університет "Харківський політехнічний інститут", 2026)
The paper analyzes the modern market of mobile applications for accounting of medicines in domestic conditions, taking into account their practical suitability for daily use. The functionality of the most common solutions is considered, in particular, the entry and storage of data on medicines, control of expiration dates, tracking of use and the implementation of reminder mechanisms. Within the framework of the work, a comparative analysis of applications was carried out, according to the results of which a predominant dependence on manual input of information by the user was revealed. It has been established that this approach reduces ease of use and increases the likelihood of errors in data entry. Based on the results of the analysis, it is concluded that there are functional limitations in the available solutions and the expediency of finding approaches to automating the processes of identification of medicines within intelligent information systems is substantiated. Figs.: 3. Refs.: 15 items.

У роботі проаналізовано сучасний ринок мобільних застосунків для обліку лікарських засобів у побутових умовах з урахуванням їх практичної придатності для щоденного використання. Розглянуто функціональні можливості найбільш поширених рішень, зокрема введення та зберігання даних про лікарські засоби, контроль термінів придатності, відстеження використання і реалізацію механізмів нагадування. У межах роботи проведено порівняльний аналіз застосунків, за результатами якого виявлено переважну залежність від ручного введення інформації користувачем. Встановлено, що такий підхід знижує зручність експлуатації та підвищує ймовірність помилок при введенні даних. За результатами аналізу зроблено висновок про наявність функціональних обмежень у наявних рішеннях і обґрунтовано доцільність пошуку підходів до автоматизації процесів ідентифікації лікарських засобів у межах інтелектуальних інформаційних систем. Іл.: 3. Бібліогр.: 15 назв.
Порівняльний аналіз сучасних мобільних застосунків для обліку та контролю лікарських засобів у побуті
Keywords: home medicine cabinet; mobile applications; market analysis; medication management; intelligent systems; automation; automation; multimodal LLMs; домашня аптечка; мобільні застосунки; аналіз ринку; інформаційні системи; облік лікарських засобів; автоматизація; інтелектуальні технології